Geographical distribution of fuel survey stations in Duhok district for the year 2024(study in transportation geography) (Wasit Journal for Human Sciences, 2025)
Fuel generating  stations are considered one of the most important and vital facilities in Duhok District, the most important of them have been increasing at the present time as a result of the increase in population and urbanization within the geographical functions in Duhok, and consequently to the economic level that increases the percentage of vehicle ownership, they are also still continuing and economically directly on the volume of consumption of petroleum products, which necessarily participates in providing fuel stations, as there is a study to reveal the geographical distribution of  fuel vehicle exploration stations within borders of Duhok District, and the extent to which this distribution is related to demographic changes, transportation networks and traffic that occur through their paths, in addition to analyzing the natural and human factors in determining the locations of their establishment and spread within the administrative borders of the study .
Keywords: Keywords : (Geographical distribution , gas stations